Improving Student Engagement in English Language Teaching through Project-Based Learning: A Classroom Action Research in a Tertiary EFL Context - Devi Annisa Marpaung; Aisyah Noor Nasution; Nelly Masna Barus; Saptari Wibowo; Ely Ezir Marpaung (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
Student engagement remains a persistent challenge in English as a Foreign Language (EFL) classrooms, particularly in contexts dominated by teacher-centred instruction that limits active learner participation. However, limited classroom-based evidence has explicitly examined how Project-Based Learning (PBL) enhances different dimensions of engagement in tertiary EFL settings. This study investigates the implementation of PBL in improving student engagement in an English teaching classroom. Employing a qualitative classroom-based design, data were collected through classroom observations, student reflective journals, and analysis of project-based learning artifacts over one instructional cycle. The study focuses on three dimensions of engagement: behavioural, emotional, and cognitive. The findings reveal that PBL significantly enhances student engagement across all dimensions. Behaviourally, students demonstrated increased participation in collaborative tasks; emotionally, they showed higher motivation and interest; and cognitively, they engaged more deeply in problem-solving and language use. Additionally, students developed stronger communication skills and collaborative competence through authentic, project-driven activities. This study contributes to EFL pedagogy by providing empirical classroom-based evidence of PBL’s effectiveness and highlighting its role in fostering meaningful, student-centred learning environments.